Os afetos do psicoterapeuta - Brandão, Jefferson de Jesus (2022)
From Baruch Spinoza's Theory of Affects, that, among other things, highlight the human difficulty in regulating and restraining affections, we realize the importance of a cartography of this aspect of human life present in the context of psychotherapy. Thus, this work was an exploratory research that used the cartographic method as an instrument, which consists of establishing clues to map the network of connections and collectivize the cartographer's experience. The cartography takes place in a process of constitution of reality, immersing itself in the plane of experience. In other words, mapping is creating an observer's reality in the world in the refusal of a representation. In this sense, we draw a map of the affective plan of psychologists in their respective clinical praxis, following how their affections are present in the evaluation of the field and in their volitional processes. The affections map resulted from meetings with five psychotherapists, four women and one man. These people, in addition to describing experiences in the clinic, reflected on their practice during the meetings. We discussed prejudice, ethics, self-care, work, affective expression and the essence and singularities of the psychotherapists.